Flexibility in motivated reasoning: strategic shifts of reasoning modes in covariation judgment - Mata, André; Ferreira, Mário B.; Sherman, Steven J. (Social cognition, 2013)
Research on motivated reasoning has shown that people with certain preferred conclusions sometimes treat information in different ways, depending on what best serves those conclusions. However, this research has focused mostly on between-subjects differences, that is, motivated selection of different judgment strategies by different people with different preferred conclusions. There is little evidence of how flexible people are in switching judgment strategies from moment to moment depending on their motives. In our research, we used problems of covariation judgment where the favorable type of strategy changed both between- and within-subjects, across different problems. Results suggest that there is considerable flexibility in motivated reasoning, such that participants who are motivated to defend a specific conclusion strategically select, and switch between, simpler or more sophisticated reasoning modes, depending on which serves the desired conclusion.